The Commodification of Woman's Bodies in Halo.Spice’s 18+ Culinary Content - Pragita, Bryan; Nurhadi, Muizzu; Sheila Puspa Ayu Saraswati Rudita; Lutfiah Indriani (CV. Era Digital Nusantara, 2025)
This study aims to analyze the influence of social media on the consumption of 18+ culinary content presented by Halo.Spice. In this context, Halo.Spice is a platform that utilizes visual appeal and unique narratives to influence consumer preferences and behavior towards exclusive culinary content. This study uses ethnographic approach with a case study method and Digital Sexual Identity framework proposed by Jessica Ringrose, involving data analysis from in-depth interviews with active users and observations of Halo.Spice social media content. The research findings reveal that Halo.Spice’s 18+ culinary content fundamentally functions as a site for the commodification of the female body, achieved through visual fragmentation and objectification. Instead of being just a marketing tool, the body becomes a key digital product used to boost audience participation. Moreover, the study highlights a multifaceted process of audience negotiation. Consumers interpret the content through a lens of modern creative freedom while navigating the tensions between digital expression and existing traditional cultural norms. This demonstrates how niche culinary media becomes a space in which gender representation, commodification and cultural values are contested and reinterpreted by consumers. However, this study has limitations in terms of population coverage, where only certain social media users are the focus of the analysis. The conclusion of this study emphasizes the importance of the role of social media in shaping culinary content consumption patterns and its potential influence on audience behavior and preferences towards sensuality and adult content.